TINJAUAN DIGITAL MARKETING TERHADAP MINAT BELI DAN KEPUTUSAN PEMBELIAN PRODUK KOSMETIK - Gusti Ayu Oviani; Murti, Ida Bagus Teguh Teja; Yogatama, I Made Wahyu (Institut Teknologi dan Kesehatan Bintang Persada, 2025)
The implementation of digital marketing makes it easier for potential consumers to obtain product information and conduct online transactions for various products, including cosmetics. Several studies have investigated the relationship between digital marketing and purchasing interest and decisions for cosmetic products, yielding positive results. By understanding how digital marketing influences purchasing interest and purchasing decisions comprehensively, businesses can design more effective and consumer-oriented marketing strategies. The method used in this review is a literature study by searching for articles from primary data sources over the past five years using related keywords. Articles included in this review were those that met the inclusion and exclusion criteria. The results of the study of 14 articles are presented in a table based on the author's name, year, title, objectives, methods, and findings. The relationship between digital marketing and purchasing interest and purchasing decisions for cosmetic products indicates that digital marketing has a positive and significant contribution in influencing consumers. Efforts are needed to improve digital literacy for both businesses and the public to optimally adapt to digital marketing platforms.